Shape of tropoelastin, the highly extensible protein that controls human tissue elasticity - Baldock, Clair (National Academy of Sciences, 2011)
Elastin enables the reversible deformation of elastic tissues and can withstand decades of repetitive forces. Tropoelastin is the soluble precursor to elastin, the main elastic protein found in mammals. Little is known of the shape and mechanism of assembly of tropoelastin as its unique composition and propensity to self-associate has hampered structural studies. In this study, we solve the nanostructure of full-length and corresponding overlapping fragments of tropoelastin using small angle X-ray and neutron scattering, allowing us to identify discrete regions of the molecule. Tropoelastin is an asymmetric coil, with a protruding foot that encompasses the C-terminal cell interaction motif. We show that individual tropoelastin molecules are highly extensible yet elastic without hysteresis to perform as highly efficient molecular nanosprings. Our findings shed light on how biology uses this single protein to build durable elastic structures that allow for cell attachment to an appended foot. We present a unique model for head-to-tail assembly which allows for the propagation of the molecule’s asymmetric coil through a stacked spring design.